การออกแบบและพัฒนาเทคนิคการเขียนโปรแกรมจาวาโดยใช้ตัวแปรเมทอด - วชิราวุธ ธรรมวิเศษ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
A method variable is developed with Java. The method variable can store reference to any object method. Method variable does not consider a class of object. But it considers the type of parameters of that method. The referenced method can be invoked passing a function of method variable. So the method invocation will be more flexibility. A programmer can use method variable to implement the event handling and component composition in the component model. This research presents the method variable technique for Java programming to support single method variable, multiple method variable, storing method variable in file and using method variable for object in an Object Orient Database. This research constructs an Application Development Framework for Java by using method variable. This framework includes tool for construct a class of method variable, group of method variable classes for event handling and group of component classes. In the same application domain of the experiments, the source codes created by method variable technique are shorter than standard Java 1.1